2008
DOI: 10.1111/j.1365-313x.2008.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

A membrane‐bound NAC transcription factor NTL8 regulates gibberellic acid‐mediated salt signaling in Arabidopsis seed germination

Abstract: SummaryGibberellic acid (GA) plays a key role in seed germination through coordinate interactions with other growth hormones and external signals. However, the way in which external signals are incorporated into the GA-signaling pathway is largely unknown. Here, we demonstrate that a membrane-bound NAC transcription factor NTL8 mediates the salt regulation of seed germination via the GA pathway, primarily independently of ABA. NTL8 is induced by high salinity. Its expression is also elevated by a GA biosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 36 publications
(46 reference statements)
6
150
0
Order By: Relevance
“…Controlled proteolytic release of membrane-bound transcription factors is emerging as a versatile way of inducing rapid transcriptional changes in plants, e.g., in response to environmental changes (26). Recently, the functions of several membranebound NAC transcription factors were documented as well as their stimulus-dependent nuclear translocation (34)(35)(36)(37). The Cvi FSQ6/ANAC089 protein lacks the membrane anchor because of the premature stop mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled proteolytic release of membrane-bound transcription factors is emerging as a versatile way of inducing rapid transcriptional changes in plants, e.g., in response to environmental changes (26). Recently, the functions of several membranebound NAC transcription factors were documented as well as their stimulus-dependent nuclear translocation (34)(35)(36)(37). The Cvi FSQ6/ANAC089 protein lacks the membrane anchor because of the premature stop mutation.…”
Section: Discussionmentioning
confidence: 99%
“…A novel wheat NAC TF, TaNAC4 was found to be induced in response to cold, salt, wounding, ABA, ethylene and MeJA, suggesting a significant cross-talk between abiotic and biotic stress conditions (Xia et al, 2010). Kim et al (2008) reported that a salt-inducible NTL8 (membrane associated NAC) regulates gibberellic acid -mediated salt signaling in seed germination. Very recently a membrane associated NAC TF from foxtail millet was found to be upregulated in drought, salinity, ethephone and MeJA treatments (Puranik et al, 2011).…”
Section: The Nac (Nam Ataf and Cuc) And Zf-hd (Zinc-finger Homeodomamentioning
confidence: 99%
“…Fourteen of the NAC transcription factors in Arabidopsis are membranebound transcription factors with transmembrane domains (Kim et al, 2007a;Liang et al, 2015). Among them, NAC with Transmembrane Motif1 (NTM1) has been reported to participate in the regulation of cell division (Kim et al, 2006), NTM1-like6 (NTL6) is involved in the regulation of pathogen resistance response (Seo et al, 2010), NTL14/ANAC089 controls ER-stress-induced programmed cell death (Yang et al, 2014), NTL4 participates in heat-stress response (Lee et al, 2014), NTL1/ANAC013 is involved in oxidative stress response (De Clercq et al, 2013), and NTL8 regulates salt-responsive flowering and seed germination (Kim et al, 2007b(Kim et al, , 2008.…”
mentioning
confidence: 99%